2008
DOI: 10.1103/physrevlett.100.095901
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Driven Stabilization of Energetically Unstable Crystal Structures Explained from First Principles Theory

Abstract: Conventional methods to calculate the thermodynamics of crystals evaluate the harmonic phonon spectra and therefore do not work in frequent and important situations where the crystal structure is unstable in the harmonic approximation, such as the body-centered cubic (bcc) crystal structure when it appears as a high-temperature phase of many metals. A method for calculating temperature dependent phonon spectra self consistently from first principles has been developed to address this issue. The method combines… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
321
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(329 citation statements)
references
References 24 publications
7
321
0
1
Order By: Relevance
“…22 They exhibit one or several dynamically unstable phonon modes which are characterized by imaginary harmonic frequencies. 23 These phonon modes are dynamical precursors of the ionic displacements and cause the transition when the temperature is lowered.…”
Section: Resultsmentioning
confidence: 99%
“…22 They exhibit one or several dynamically unstable phonon modes which are characterized by imaginary harmonic frequencies. 23 These phonon modes are dynamical precursors of the ionic displacements and cause the transition when the temperature is lowered.…”
Section: Resultsmentioning
confidence: 99%
“…Harmonic phonon spectrum is calculated with a finite-difference supercell approach, 70 and roomtemperature phonon spectrum is obtained by taking into account anharmonic phonon-phonon interaction with a selfconsistent ab initio lattice dynamical method. 71 To give an evaluation of photovoltaic performance of the selected optimal materials, the theoretical maximum solar cell efficiency, i.e., -spectroscopic limited maximum efficiency (SLME)‖ 72 Figure 2a shows their calculated total energies for the case of Cs 2 AgBiCl 6 . Clearly the most stable configuration F is the standard doubleperovskite structure (in space group of Fm-3m) with M + X VII 6 and M 3+ X VII 6 alternating along the three crystallographic axes and forming the rock-salt type ordering.…”
Section: Methodsmentioning
confidence: 99%
“…We find that the harmonic phonon spectra of Cs 2 InBiCl 6 and Cs 2 InSbCl 6 (at 0 K) show substantial imaginary optical modes (black lines in Figure S3a and S3b). However when we take into account phonon-phonon interaction (anharmonic effect) at room temperature (300 K), 71 all the imaginary phonons disappear (red lines in Figure S3a and S3b). The results indicate that Cs 2 InBiCl 6 and Cs 2 InSbCl 6 are dynamically stable under ambient condition.…”
Section: Combinatory Materials Screening Of Potentially Highphotovoltmentioning
confidence: 99%
“…Very recently, Leonov et al 24 extended DMFT calculations to the high-temperature δ-Fe and found within QHA an instability of the bcc lattice, suggesting the necessity of including other anharmonic effects for a correct description of δ-Fe. Anharmonicity in the lattice subsystem, i.e., the phonon-phonon interactions 25 , is especially important close to the melting point, as was seen in the bcc phases of the group 3 (Sc, Y, La) and 4 (Ti, Zr, Hf) metals [26][27][28][29] . Whether the anharmonic lattice effect is crucial in the case of iron remains to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%